Governing transnational water and climate risks in global supply chains - Gustafsson, Maria Therese; Schilling-Vacaflor, Almut; Pahl-Wostl, Claudia (Earth System Governance, 2024)
Interlinked water and climate impacts are increasingly crossing borders via global supply chains. A recent wave of supply chain regulations, based on human rights and environmental due diligence (HREDD), has emerged with the goal of holding companies accountable for adverse impacts throughout their supply chains. We develop an analytical framework to theorize how key factors grounded in domestic contexts shape how companies put HREDD in practice, focusing on water and climate risks. Our framework distinguishes between knowledge and transparency; domestic policies; and actor constellations and power. We apply this framework to study how large agricultural producers in Brazil (mal-)adapt to increasing water scarcity and climate change impacts, contributing to local water conflicts. Subsequently, we analyze how multinational companies have addressed these domestic factors in their HREDD systems. Our study provides a nuanced understanding of current trends and challenges of transnational business governance to effectively target cross-scalar climate and water risks.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Agriculture; Brazil; Governance; Planetary justice; Supply chain regulations